Cervical dysplasia and HIV type 1 infection in African pregnant women: a cross sectional study, Kigali, Rwanda. The Pregnancy and HIV Study Group (EGE). Issue 2 (1st April 1999) - Leroy, V; Ladner, J; De Clercq, A; Meheus, A; Nyiraziraje, M; Karita, E; Dabis, F
Abstract : OBJECTIVE: To study the prevalence of cervical squamous intraepithelial lesions (SILs) and their association with HIV-1 infection and immunodeficiency among pregnant women in Kigali, Rwanda. METHODS: As part of a cohort study on the impact of HIV-1 infection on pregnancy outcome, HIV-1 seropositive (HIV+) and seronegative (HIV-) pregnant women were enrolled during the last trimester of pregnancy at the maternity ward of the Centre Hospitalier de Kigali from July 1992 to August 1993. At inclusion, women were screened for sexually transmitted diseases (STDs)–syphilis, Neisseria gonorrhoeae, chlamydia trachomatis, Trichomonas vaginalis. CD4+ lymphocyte counts were measured and a Papanicolaou smear performed. RESULTS: Papanicolaou smear was interpretable in 103 HIV+ women and 107 HIV- women. Prevalence of SILs was significantly higher in HIV+ women than in HIV- women: 24.3% v 6.5% (odds ratio = 4.6; 95% CI: 1.8-12.3). SIL+ women (n = 32) tended to have more STDs than SIL- women (n = 178), but this did not reach a statistical difference: 37.5% and 24.7% respectively (p = 0.13). They also had a mean CD4 count significantly lower than SIL- women (623 and 784 CD4+ cells x 10(6)/l, respectively; p = 0.02). CONCLUSION: SILs were HIV related and the association with immunosuppression was statistically significant. Prevalence of SILs was high in this population of pregnant women with high HIV/STDs prevalence. Screening policy for STDs and SILs in African women should be assessed in prenatal care.